Enduring effects of tacrine on cocaine-reinforced behavior: Analysis by conditioned-place preference, temporal separation from drug reward, and reinstatement. (July 2015) - Grasing, Kenneth; Yang, Yungao; He, Shuangteng
Graphical abstract: Abstract: Previous work by our laboratory has shown that tacrine can produce long-lasting reductions in cocaine-reinforced behavior, when administered to rats as daily intravenous infusions over four days. Tacrine causes dose-related liver toxicity in different species, and its manufacture for human use was recently discontinued. This study was conducted to further characterize its actions on cocaine reward. Cocaine-experienced animals that had no contact with drug over one week resumed self-administration at levels similar to their initial baseline. When tacrine was administered over four days which were preceded and followed by washout periods to allow elimination of cocaine and tacrine respectively, subsequent cocaine self-administration was attenuated by more than one-half. Tacrine administered at 10 mg/kg-day as a chronic infusion by osmotic pump did not modify cocaine-induced increases in locomotor activity or conditioned-place preference. In rats that exhibited persistent attenuation of cocaine-self-administration after receiving tacrine, cocaine-induced reinstatement was also attenuated. No changes in plasma measures of renal or hepatic function were observed in rats receiving tacrine. In conclusion, pretreatment with tacrine can decrease cocaine-motivated behavior measured by self-administration or reinstatement, but not conditioned-place preference. Reductions in cocaine self-administration following pretreatment with tacrine do not require direct interaction with cocaine and are not secondary to either liver or kidney toxicity.